RISKS OF ORAL NON-STEROIDAL ANTI-INFLAMMATORY DRUGS USE IN PATIENTS WITH INTESTINAL STOMA: DO BRAZILIANS LEAFLETS TALK ABOUT IT? - Bunnel, Kitete Tunda (Congresso Paulista de Estomaterapia, 2024)
Introduction: Creating an intestinal stoma involves redirecting a section of the intestine to the skin's surface, commonly performed in conditions such as colorectal cancer, inflammatory bowel disease, and diverticular disease (1). While nonsteroidal anti- inflammatory drugs (NSAIDs) are extensively used, their association with gastrointestinal toxicity poses risks, particularly in patients with stomas like ileostomies or colostomies (2). NSAIDs can disrupt fluid and electrolyte balance, increase susceptibility to gastrointestinal bleeding hinder wound healing, alter medication absorption, and conceal infections, impacting patients' quality of life (3). Objective: To analyze and assess Brazilian NSAID leaflets for information on cautious NSAID use in stoma patients. Method: This is a documental study, where a comprehensive review of NSAID product leaflets in Brazil (celecoxib, diclofenac, ibuprofen, meloxicam, naproxen and nimesulide) was conducted. The leaflets were extracted from the official website of the Brazilian Health Regulatory Agency (Anvisa, access at: https://portal.anvisa.gov.br) and the gathered information focused on the presence or not of specific warnings or precautions related to stoma patients in using oral NSAIDs. Results: We retrieved six leaflets of oral NSAIDs, and none (0%) provided information about specific warnings or precautions related to stoma patients using NSAIDs. However, 33.3% of the leaflets have information about the maximum time of use of oral NSAIDs while 66.7% of them talked about the risks of misidentifying infections related to NSAID use. We also have 66.7% that provided recommendations for dosage adjustments or alternative therapies. Conclusion and Contributions to Enterostomal Therapy: The Brazilian NSAID leaflets have a notable absence of specific cautions for patients with intestinal stomas. Addressing this gap is crucial to ensure the safe and effective use of NSAIDs in this vulnerable patient population. Further research and regulatory efforts may be needed to improve the comprehensiveness of patient information provided in NSAID leaflets.